Functional characterization of neurons in the early visual pathway: An exploration of spike train classification methods - Fontes, Cássio Mendes; Turchetti-Maia, Ana Luiza; Baron, Jerome; Braga, Antônio Pádua (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS), 2010)
The understanding of how neurons interact in the visual cortex and what kinds of neurons are responsible for each interaction are still unanswered questions in the field of neurophysiology. To acquire information on such problems, sixteen neurons were mapped with visual stimulus of different sizes, contrasts but with similar patterns on their receptive fields. The data obtained was analyzed with several approaches. PCA was applied as a linear dimensionality reduction technique and the new data was separated with clustering techniques. The acquired data was also represented as the difference of time (moment in time when one spike occured minus the previous one) between spikes. Several attributes were extracted and clustered into different groups and with kernel techniques to visualize the data two large groups of neurons were identified. A support vector machine classifier (SVMC) was implemented in order to verify if an efficient classification could be performed. The main data was also separated as spikes before, during and after direct stimulation using the difference of time between spikes as data. The same attributes were extracted from these matrices and kernel techniques were applied on them to visualize the data. As before, two large groups of data were identified and isolated with clustering techniques which represented two groups of neurons.